Preparation, characterization, and antimicrobial activity of ferrocene‐containing polymeric materials. Issue 7 (18th September 2020) - Zampino, Daniela; Pedotti, Sonia; Ussia, Martina; Dattilo, Sandro; Mancuso, Monique; Zaccone, Renata; Patti, Angela
Abstract: Ferrocenyl(benzyl) imidazole (FcIm) and two related methyl‐imidazolium salts (FcMIm + I – and FcMIm + PF6 – ) were synthesized for their incorporation into plasticized PVC by solvent casting technique. The obtained materials were investigated for their thermal stability and, compared to pure polymer, films containing ionic ferrocene derivatives in 0.5% w/w loading were found slightly more stable. The pure ferrocene compounds showed antibacterial activity against Staphylococcus epidermis, but not against Escherichia coli, with a maximum for FcMIm + PF6 – salt. After incorporation into PVC polymer, antibacterial activity against S . epidermis was observed (by disk diffusion test) only for PVC/FcMIm + PF6 – (5% w/w) film, from which a release of 14.6% of the ferrocenilimidazolium cation in aqueous medium was measured after 24 hr. Abstract :